TIPOLOGI KLITIK PRONOMINA: STUDI KOMPARATIF SINTAKSIS BAHASA SASAK DIALEK MENO-MENE DAN GRAMATIKA BAHASA INDONESIA DI DESA AIK MUAL KECAMATAN PRAYA KABUPATEN LOMBOK TENGAH - Aini, Ahsanul; Ernawanti; Anggraini Putri, Juhani; Hidayah, Nurul; Pardini, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the comparative typology of pronoun clitics between the Meno-Mene dialect of Sasak language and Indonesian through a syntactic review. Using a qualitative descriptive method with contrastive analysis, this research examines the form, position and function of clitics as markers for clause arguments based on speech data from the people of Aik Mual Village. The results of the analysis show that Sasak pronoun clitics (/-k/, /-m/, /-n/, /-t/) are very productive as subject markers in verbal predicates and adjectives. This is typologically different from Indonesian which does not recognize subject clitics in nonverbal predicates and must use free pronouns. Although both languages ​​show functional similarities in object and possessive enclitics, Sasak has more flexible syntactic integration than Indonesian, which has a more limited distribution.